Social problems surrounding health at SADA and the role of the church in effecting redress - Sabsana, M (Department of Religious Studies, 2023)
The aims will be double-pronged for we are dealing with divergent and yet complementary issues of history and how they inform the present situation and circumstances. The area of focus is Sada (Eastern Cape), and yet the study was informed by experiences outside the region. This study, an exploration of the complex sociological problems and health phenomenon in particular, at Sada, with its national relevance is multi-layered in its aims.